Analisa Keselamatan dan Kesehatan Kerja Proyek Gedung WWTP Dengan Metode Hirarc Di PT. Huathai Construction Indonesia - Shandynavia Arji Nandi Tami; Agus Syahabuddin; Muhammad Yusuf (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2024)
The WWTP Building Construction Project is one of the projects engaged in the construction sector, where in the process there are various potential hazards that have an impact on work accidents and even occupational diseases (PAK). Therefore, with the Hazard Identification, Risk Assessment And Risk Control (HIRARC) method is a worksheet that is appropriate or can be applied to the construction of the WWTP Building. The purpose of this study is to determine the potential hazards and assess the K3 risk in the construction of the WWTP Building. This type of research uses a quantitative method with a descriptive-observational approach and a survey study design because it provides an overview of the potential hazards and risks in the construction of the WWTP Building using the HIRARC method. The results of the study showed that in the lightweight brick installation process, 20 potential hazards were identified, while the highest risk category was high risk 52% and the highest risk category was extreme risk 14%. In the plaster and cement wall work, 4 potential hazards were identified, while the highest risk category was moderate risk 60% and the highest risk category was high risk 40%. In ceramic work, 10 potential hazards were identified, while the highest and most risk categories were high risk 67%. In the gypsum partition wall work, 11 potential hazards were identified, while the highest risk category was moderate risk 56% and the highest risk category was extreme risk 22%. In the ladder work, 28 potential hazards were identified, while the highest risk category was moderate risk 47% and the highest risk category was extreme risk 24%.